Effect of Nitrogen and Sulfur on the Growth and Yield of Sesame - Shilpi, Sonia; Islam, M. N.; Sutradhar, G. N. C.; Husna, Asmaul; Akter, Fahmina (International Journal of Bio-resource and Stress Management, 2012)
An experiment was conducted in the field of Sher-e-Bangla Agricultural University farm, Sher-e-Bangla Nagar, Dhaka, Bangladesh during the period from February to May, 2009 to determine the effect of nitrogen and sulfur on growth and yield of sesame. The experiment consisted of two factors. 4 levels of nitrogen N0: 0 kg N ha-1 (control); N1: 40 kg N ha-1; N2: 60 kg N ha-1 and N3: 100 kg N ha-1; and 4 levels of sulfur S0: 0 kg S ha-1 (control); S1: 20 kg S ha-1; S2: 40 kg S ha-1 and S3: 60 kg S ha-1. Plant height, number of branches plant-1, number of leaves plant-1, seed yield, Stover yield were increased significantly with increasing N level upto 60 kg N ha-1 (N2) . On the other hand, plant height, number of branches plant-1, number of leaves plant-1 and seed yield were increased significantly with increasing S level upto 40 kg S ha-1 (S2) whereas Stover yield was increased upto 60 kg S ha-1. Interaction effects of nitrogen(60 kg P ha-1) and sulphur (40 kg S ha-1 ) gave the highest number of capsules plant-1 (70.40), length of capsule(3.99cm) , diameter of capsule(2.77cm), seeds capsule-1(50.63) and thousand seed weight(12.25g). The combined application of 60 kg nitrogen and 40 kg Sulphur may be considered to be optimum for getting higher yield of sesame.